The practice and determining factors of voluntary graphics disclosure in Local Government Financial Statements in Indonesia - Probohudono, Agung Nur; Supriyanto, Supriyanto; Kurniawati, Estetika Mutiaranisa (Asian Journal of Accounting Perspectives, 2021)
Research aim: This study aims to measure the extent and the determinants of voluntary graphics disclosure in Laporan Keuangan Pemerintah Daerah (LKPD) or Local Government Financial Statements in Indonesia. Design/ Methodology/ Approach: This study used 197 audited LKPD in Indonesia, comprising 155 regency governments and 32 district governments. The financial statements of these 197 local governments were examined to measure the extent of voluntary graphics disclosure and investigate the potential determinants of voluntary graphics disclosure. This study used multiple regression analysis to examine the determinants (performance, level of dependency, location, education background, and competency) of voluntary graphics disclosures. Research findings: The results indicate a low extent of voluntary graphics disclosure in the LKPD in Indonesia. The average voluntary graphics disclosure rate is 44.88%, demonstrating a lack of usage of voluntary graphics disclosure. The results also indicate that only performance has an insignificant effect on the extent of voluntary graphics disclosure. Practitioner/ Policy implication: The findings regarding voluntary graphics disclosure in LKPD should be of concern to regulatory authorities and standard setters in Indonesia. Research limitation: This study focuses on measuring the extent and the determinants of voluntary graphics disclosure practices among 197 local governments in Indonesia. Hence, the sample of this study is limited to the local governments employing graphics in providing information in their financial statements for the year 2015. Keywords: Local Government Financial Statements, Local Government, Voluntary Graphics Disclosure Type of article: Research paper JEL Classification: H70